Unexpected complexity in the interference activity of a cloned influenza defective interfering RNA - Bo Meng (Virology Journal, 2017)
Abstract Background Defective interfering (DI) viruses are natural antivirals made by nearly all viruses. They have a highly deleted genome (thus being non-infectious) and interfere with the replication of genetically related infectious viruses. We have produced the first potential therapeutic DI virus for the clinic by cloning an influenza A DI RNA (1/244) which was derived naturally from genome segment 1. This is highly effective in vivo, and has unexpectedly broad-spectrum activity with two different modes of action: inhibiting influenza A viruses through RNA interference, and all other (interferon-sensitive) respiratory viruses through stimulating interferon type I. Results We have investigated the RNA inhibitory mechanism(s) of DI 1/244 RNA. Ablation of initiation codons does not diminish interference showing that no protein product is required for protection. Further analysis indicated that 1/244 DI RNA interferes by replacing the cognate full-length segment 1 RNA in progeny virions, while interfering with the expression of genome segment 1, its cognate RNA, and genome RNAs 2 and 3, but not genome RNA 6, a representative of the non-polymerase genes. Conclusions Our data contradict the dogma that a DI RNA only interferes with expression from its cognate full-length segment. There is reciprocity as cloned segment 2 and 3 DI RNAs inhibited expression of RNAs from a segment 1 target. These data demonstrate an unexpected complexity in the mechanism of interference by this cloned therapeutic DI RNA.